Intraarterial digital subtraction angiography for definitive diagnosis of intracranial aneurysms. - Touho, H; Karasawa, J; Tazawa, T; Nakagawara, J; Yamada, K; Kobayashi, K; Asai, M; Kagawa, M; Yasue, H (American Journal of Neuroradiology, 1988)
Comparisons between digital subtraction angiography and conventional angiography have frequently been made in the radiologic literature, and the high quality and several advantages of the former have been reported. In this study, 101 patients with intracranial aneurysms were examined only by intraarterial digital subtraction angiography; no conventional angiography was used. High-quality images were consistently obtained, facilitating an accurate and definitive diagnosis of intracranial aneurysm. Magnification radiography and stereography using intraarterial digital subtraction angiography were done to obtain a more precise diagnosis. Five small intracranial aneurysms with diameters of 1.0 to 2.0 mm could be detected. The procedure was considered to be as reliable and as safe as conventional angiography, used previously. Important advantages of intraarterial digital subtraction angiography include reduced procedural time and decreased contrast agent burden, factors that will ensure broader application of this procedure for definitive diagnosis of intracranial aneurysms as experience with the technique accumulates.